CHARACTERIZATION OF STREPTOMYCES SCABIES ISOLATED FROM COMMON SCAB LESIONS ON POTATO TUBERS BY MORPHOLOGICAL, BIOCHEMICAL AND PATHOGENICITY TESTS IN CHLEF REGION IN WESTERN ALGERIA (Sciences & Technologie. C, Biotechnologies, 2007)
In summer 2002, nine isolates causing common scab symptoms were collected from tubers presenting superficial and raised corky lesions on tubers surface in number of locations from the Chlef region in Algeria. The common scab inducing organismwere characterized by creamy colonies on yeast malt extract (YMA) and by arial mycelium which turned brown with age. The organism was Gram positive, non motile, utilized L-arabinose, D-fructose, D-glucose and rhamnose. They degraded the xylose and starch with production of melanin on peptone yeast extract agar-iron(PYI). Additionally, it was determined that most strains obtained from differents locations were identical in morphology and biochemical characteristics. Furthermore, these isolatesshares most pattern with the reference isolate ATCC49173. Results of pathogenicity tests showed that all isolates were pathogenic on both cultivars(Desiree and Claustar) causing symptoms with aggressiveness of strains varying from mild to moderately severe. Koch’s postulates for isolates were also fulfilled.